2008
DOI: 10.4070/kcj.2008.38.3.179
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Successful Primary Percutaneous Coronary Intervention in Patients With an Anomalous Right Coronary Artery Arising From the Left Coronary Cusp

Abstract: An anomalous origin of the right coronary artery (RCA) from the left coronary cusp is a rare congenital anomaly. Because of the unusual location and the noncircular luminal orifice of this anomaly, cannulation of this artery during coronary angiography and percutaneous coronary intervention (PCI) poses significant technical difficulties when using the currently available guiding catheters. Primary PCI should be performed as quickly as possible when a patient displays this condition. When we face the situation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…There are no standardized guidelines for catheter selection for this technically challenging scenario. A method similar to ours has been reported -a hair dryer was used to heat an EBU guiding catheter to facilitate manual manipulation in that case [1]. More recently, it has been suggested that knowledge of the anatomic origin of the anomalous RCA within the aortic root may provide additional guidance [2].…”
mentioning
confidence: 81%
“…There are no standardized guidelines for catheter selection for this technically challenging scenario. A method similar to ours has been reported -a hair dryer was used to heat an EBU guiding catheter to facilitate manual manipulation in that case [1]. More recently, it has been suggested that knowledge of the anatomic origin of the anomalous RCA within the aortic root may provide additional guidance [2].…”
mentioning
confidence: 81%
“…Associated findings support the suggestion that the pulmonary artery has little or no effect on the constriction of coronary blood flow. Percutaneous coronary intervention (PCI)20)46)47) relieves systolic compression, but selective cannulation and stent insertion in the anomalous RCA are difficult to perform due to the small, ectopic orifice and the long, curved intramural portion of the anomalous RCA. Prior to PCI, the anomalous RCA must be evaluated by MDCT; MDCT-guided cannulation is helpful in selective cannulation and intervention 20)21).…”
Section: Surgical Methodsmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI)20)46)47) relieves systolic compression, but selective cannulation and stent insertion in the anomalous RCA are difficult to perform due to the small, ectopic orifice and the long, curved intramural portion of the anomalous RCA. Prior to PCI, the anomalous RCA must be evaluated by MDCT; MDCT-guided cannulation is helpful in selective cannulation and intervention 20)21). Coronary artery bypass grafting (CABG)32)48) is technically easy because it does not entail opening of the aorta or manipulation of the intercoronary commissure.…”
Section: Surgical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of physicians who use this method to display vessels with origin abnormality is steadily increasing. In our laboratory, we also use catheter reshaping since long time for cases where the existing catheters are inadequate for the imaging of vessels with origin anomalies [7,8].…”
Section: Introductionmentioning
confidence: 99%